Fruits of grace. The ecumenical experience of the Community of Grandchamp - Vries, Mink de, 1962- (Lutterworth Press, 2018)
Before Taizé, there was Grandchamp. The lesser-known Protestant women's community, initiated in 1936, grew out of generations of women's groups in French-speaking Switzerland. It was heavily influenced by Wilfred Monod, the Student Christian Movement, Swiss Reformed efforts at liturgical renewal, and Bonhoeffer's Life Together. It was so deeply affected by the angst generated by World War II and the search by European Christians for new ways to be Christian. The Fruits of Grace, authored by the third prioress of the Community of Grandchamp in Switzerland, reflects on the origins of the community, the sources and development of its spirituality, and on its ministries. Foci include the involvement of the community in the ecumenical movement and in mission around the world. There is also important new information about its interaction with Taizé, Roman Catholic religious communities, and the women themselves, as individuals and as a community. Sister Minke de Vries provides an intimate view into the inner workings of a women's community and the structures of the spiritual practices of the Community of Grandchamp. It is a powerful analysis of a European Protestant women's monastic community.